PENGARUH SUHU DAN LAMA PEMANASAN TERHADAP KARAKTERISTIK ORGANOLEPTIK DAN LAMA SIMPAN KASOAMI KERING - helmi, helmi; Tamrin, Tamrin; Hermanto, Hermanto (Jurnal Sains dan Teknologi Pangan, 2021)
ABSTRACKThe aim of the research was to study the effect of the interaction of temperature and heating time on organoleptic characteristics and shelf life of dry kasoami. This study used a completely randomized design (CRD) with two factors. The first factor was the heating temperature which consisted of three levels, namely S1 (heating temperature of 75ºC), S2 (heating temperature of 85ºC), and S3 (heating temperature of 95ºC). Meanwhile, the second factor was the heating time which consisted of three levels, namely L1 (0.75 hours of heating time). L2 (1 hour heating time) and L3 (1.25 hours heating time) with a vacuum pressure of 70 cmHg. Observation variables were shelf life using an organoleptic testing method for 21 days, moisture content, and hedonic organoleptic testing (color, aroma, taste, and texture). Data analysis was done using Analysis of Variance. The result with a significant effect on the observed variables was followed by Duncan's Multiple Range Test (DMRT) at a 95% confidence level (α=0.05). The results show that the dry cassava product with a vacuum heating temperature of 85ºC and 1 hour heating time (S2L2) had the highest organoleptic assessment with average scores of color, aroma, and taste reached 3.80 (like), 3.96 (like), and 4.36 (like), respectively. Meanwhile, the S3L3 treatment (a vacuum heating temperature of 950C and 1.25 hours heating time) had the highest score of texture that reaching 3.76 (like). Dry kasoami S3L3 had a shelf life of up to 21 days with a moisture content of 6.32%.Keyword: Kasoami, cassava, vacuum fryingABSTRAKPenelitian bertujuan untuk mempelajari pengaruh interaksi suhu dan lama pemanasan terhadap karakteristik organoleptik dan umur simpan kasoami kering. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL), dengan 2 faktor. Faktor pertama adalah suhu pemanasan yang terdiri dari 3 taraf yaitu S1 (pemanasan suhu 75ºC), S2 (pemanasan suhu 85ºC), S3 (pemanasan suhu 95ºC) dan faktor kedua adalah lama pemanasan terdiri dari 3 taraf yaitu L1 (lama pemanasan 0,75 jam), L2 (lama pemanasan 1 jam) dan L3 (lama pemanasan 1,25 jam) dengan tekanan vakum berkisar 70 cm Hg. Variabel pengamatan yaitu lama simpan dengan metode pengujian organoleptik selama 21 hari, kadar air, dan uji organoleptik hedonik (warna, aroma, rasa dan tekstur). Analisis data menggunakan sidik ragam (Analysis of Varian). Penilaian organoleptik yang berpengaruh nyata terhadap variabel pengamatan, dilanjutkan dengan uji Duncan’s Multiple Range Test (DMRT) pada taraf kepercayaan 95% (α=0,05). Hasil penelitian menghasilkan kesimpulan produk kasoami kering dengan perlakuan suhu pemanasan vakum 85ºC dan lama pemanasan (S2L2) menjadi perlakuan terbaik untuk warna, aroma dan rasa dengan nilai warna 3,80 (suka), aroma 3,96 (suka), dan rasa 4,36 (suka) dan perlakuan suhu pemanasan vakum 950C dan lama pemanasan 1,25 jam (S3L3) menjadi perlakuan terbaik untuk tekstur dengan nilai 3,76 (suka). Kasoami kering perlakuan S3L3 memiliki umur simpan sampai hari ke-21 dengan kadar air sebesar 6,32 %.Kata kunci: Kasoami, ubi kayu, penggorengan vakum.